Local Relationship between Global-Flash Multifocal Electroretinogram Optic Nerve Head Components and Visual Field Defects in Patients with Glaucoma - Moon, Chan Hee (J Ophthalmol, 2015)
Purpose. To investigate the local relationship between quantified global-flash multifocal electroretinogram (mfERG) optic nerve head component (ONHC) and visual field defects in patients with glaucoma. Methods. Thirty-nine patients with glaucoma and 30 normal controls were enrolled. The ONHC amplitude was measured from the baseline to the peak of the second positive deflection of the induced component. The ONHC amplitude was normalized by dividing ONHC amplitude by the average of seven largest ONHC amplitudes. The ONHC amplitude ratio map and ONHC deficiency map were constructed. The local relationship between the ONHC measurements and visual field defects was evaluated by calculating the overlap between the ONHC deficiency maps and visual field defect plots. Results. The mean ONHC amplitude measurements of patients with glaucoma (6.01 ± 1.91 nV/deg(2)) were significantly lower than those of the normal controls (10.29 ± 0.94 nV/deg(2)) (P < 0.001). The average overlap between the ONHC deficiency map and visual field defect plot was 71.4%. The highest overlap (75.0%) was between the ONHC ratios less than 0.5 and the total deviations less than 5%. Conclusions. The ONHC amplitude was reduced in patients with glaucoma compared to that in normal controls. Loss of the ONHC amplitude from the global-flash mfERG showed a high local agreement with visual field defects in patients with glaucoma.